1984
DOI: 10.1172/jci111544
|View full text |Cite
|
Sign up to set email alerts
|

Generation of nitrogen-chlorine oxidants by human phagocytes.

Abstract: Abstract. Human phagocytes can be triggered to generate large quantities of long-lived nitrogen-chlorine derivatives. This class of oxidants can be detected as early as 5 min after the addition of phorbol myristate acetate or opsonized zymosan particles. Unlike all other oxygen metabolites known to be generated by phagocytes, the nitrogen-chlorine compounds can be readily detected in cell supernatants 90 min after stimulation. The generation of these oxidants is linear with neutrophil concentration, favored at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(69 citation statements)
references
References 26 publications
2
66
1
Order By: Relevance
“…It is thought that a significant fraction of the HOCl produced by the MPO system of activated neutrophils may react with endogenous amines (e.g., ammonia, taurine, and other amino acids) to yield derivatives containing nitrogen-chlorine bonds (12,19). In contrast to an earlier study (21), we find that the bactericidal potency of NH 2 Cl is slightly less, rather than more, when compared with that of HOCl.…”
Section: Vol 178 1996contrasting
confidence: 97%
“…It is thought that a significant fraction of the HOCl produced by the MPO system of activated neutrophils may react with endogenous amines (e.g., ammonia, taurine, and other amino acids) to yield derivatives containing nitrogen-chlorine bonds (12,19). In contrast to an earlier study (21), we find that the bactericidal potency of NH 2 Cl is slightly less, rather than more, when compared with that of HOCl.…”
Section: Vol 178 1996contrasting
confidence: 97%
“…Preincubating L-serine with HOCl avoided competing reactions (e.g., with amino residues on the RNase A that also might consume HOCl; refs. 22,23). For modification with the myeloperoxidase system, 60 nM myeloperoxidase, 1 mM L-serine, 1 mM H 2 O 2 , and 150 mM NaCl were incubated in buffer A at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…It involves myeloperoxidase, a heme protein secreted by activated phagocytes (19). This enzyme uses H2O2, which phagocytes also secrete, to convert chloride ion to hypochlorous acid (HOCl) (19)(20)(21) The initial product of the myeloperoxidase-H 2 O 2 -chloride system, HOCl, reacts with the amino group (RNH 2 ) of free amino acids to form a chloramine (RNHCl) (19,(22)(23)(24)(25):…”
mentioning
confidence: 99%
“…Hypochlorous acid/ hypochlorite can react with other molecules to form a variety of chlorinated oxidants (8). At least half of the neutrophil-derived chloramines result from the reaction ofHOCI/OCI-with endogenous taurine (9). Although taurine is generally thought of as an antioxidant, previous studies have demonstrated that even in the presence of high concentrations of taurine, the transformation of HOCI/OCI-to taurine chloramines does not reduce the oxidative potential of HOCI/OCl-against various chemical groups such as thiols and thioethers (10).…”
Section: Introductionmentioning
confidence: 99%